Regional well-being variations in Finland - Seppo Siirilä; Lauri Hautamäki; Jorma Kuitunen; Timo Keski-Petäjä (Geographical Society of Finland, 1990)
The research deals with the regional variations in the well-being of the population in Finland in the mid-1980's. Choosing a viewpoint of well-being can be justified by the changing role of regional structures. In a post-industrial society, there is no longer the same correlation between the old types of regional structures (the structure of production and industries, services, etc.) and the desired well-being factors (employment, livelihood, education, etc.). Consequently, there is an urgent need to explicate the significance of structural changes and policy measures for actual well-being of people in different regions and municipalities. The research has as an aim to make a general survey of the regional variations in well-being and to identify the most problematic municipalities in terms of certain important resources of well-being: employment, income, housing, education, health, and security against criminal offences. The measurement emphasizes the percentage of the disadvantaged on each scale. On the basis of their regional variation, the variables are concentrated into four concise indices which combined one or more subfactors for well-being: unemployment, 'poverty' (income, education, level of housing), 'misery' (housing space, health), and insecurity. By grouping municipalities on the basis of their structural features into municipality types, the research depicts the structural backgrounds that pose problems to well-being. The types are: (1) large population centres, (2) industrial centres, (3) suburban municipalities, (4) rural population centres, (5) industrialized rural municipalities, (6) rural commuter municipalities, (7) primary production municipalities. Unemployment is examined as a dual problem: absolute and relative. On a relative scale, the most severe problems occur in Eastern and Northern Finland. These problems affect all municipality types. The problem of unemployment in absolute figures is the most difficult in the large population centres and industrialized centres in the provinces of ...